Succeeding With Problem Faculty: A 6-Step Guide - Kent Crookston (Academic Chairpersons Conference Proceedings, 2017)
In Crookston’s recent national survey, 3,000 academic leaders identified “dealing with problem faculty” as the issue with which they most wanted help; it was their stand-alone top concern. Problem colleagues in any organization include bullies, jerks, passive-aggressives, poor performers, and those who are psychologically distressed. Crookston draws from best-selling business and leadership literature, and presents six calculated steps for effectively dealing with a challenging colleague. Participants leave this workshop with sound practical guidance on how to act when things go wrong, but more importantly how to ensure that things go right.
Keywords: problem faculty; challenging; poor performers